(The impact of technological capabilities and their role in promoting continuous improvement activities in the organization) An exploratory study of the opinions of a sample of workers in Al-Noura Factory - Holy Karbala - Mohanad Jasim Mahdi,; Safaa Abd Ali Abdulameer, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of the study to me Determine the role of technological capabilities in promoting activities Continuous improvement in Al-Noura Factory in Holy Karbala , Andcame the importance ofstudy represented by presenting a theoretical framework linking two important variables: And technological capabilities represented in their dimensions (technology knowledge, strategic capabilities in the field of technology, personal technology, inter-organizational relations, relations with suppliers, infrastructure), Andcontinuous improvement And represented by its dimensions (understanding optimization continuous, get On Usually optimization continuous, the focus On optimization continuous, Spread optimization continuous development the permanent system optimization continuous building the organization educated) Disht study on an intentional sample consisting of (155) security guy ( Engineers and technicians) was used resolution As the main tool for data collection and measuring variables The answers were analyzed to reach the final results of the research by using a set of methods statistic , building. On the measurement of the variables ofstudy Diagnosing it and testing the relationship and the effect, the statistical methods produced a number of results, perhaps the most prominent of which are: The validity of the hypothesis (There is a relationship Link and influence technology capabilities in the activities ofFor continuous improvement in the organization) did notNoura's workA number of recommendations were reached, the most important of which are: necessityNS Work to provide and enhance the efforts of engineers and technicians inrelationship investment positivity between optimization continuous What contributes to their having sufficient knowledge of modern technological capabilities and also achieves an important characteristic for them, which is the ability to adapt to modern technological changes .